The Relationship Between Cervical Curve and Endurance in Upper Trapezius Muscles - Maharani, Silvia Putri; Naufal, Adnan Faris (Universitas Negeri Semarang, 2025)
Introduction: A decrease in the cervical curve due to Forward Head Posture (FHP) can reduce the endurance of the upper trapezius muscle, which plays an essential role in supporting the head. Objectives: This study aims to determine the relationship between cervical curve and upper trapezius muscle endurance. Method: The study used a quantitative design with a cross-sectional approach, involving 36 Physiotherapy students of Universitas Muhammadiyah Surakarta. Measurement of cervical curve was done with craniovertebral angle (CVA), while muscle endurance was measured through isometric contraction with 90° shoulder abduction. Data analysis used Spearman Rank Correlation test. Result: There is a positive and significant relationship between upper trapezius muscle endurance and craniovertebral angle (CVA), with a correlation coefficient of 0.433 and a significance value (p-value) of 0.008. This shows that the better the upper trapezius muscle endurance, the more upright a person's head posture. Conclusion: A decrease in cervical curve (FHP) is associated with decreased muscle endurance, which can lead to faster fatigue and muscle soreness. This finding shows the importance of posture management in preventing musculoskeletal disorders, especially in the student population who are often exposed to prolonged device use activities.